Comparing the monitoring and evaluation systems of watershed management related development projects in Amhara, Ethiopia - Kainulainen, Aino (2012)
Natural resource degradation is both a cause and a result of poverty in Ethiopia. Therefore it is important to include watershed management into efforts to reduce poverty and food insecurity in the country. In order to see if different interventions are effective in restoring the degraded environment, it is important to have a functioning monitoring and evaluation system that includes natural resource degradation and other environmental factors.